INTEGRATION OF GEOLOGY AND PETROLEUM ENGINEERING ASPECTS FOR CARBONATES ROCK TYPING - Andy Setyo Wibowo (Testing Center for Oil and Gas LEMIGAS, 2013)
Carbonate rocks are highly heterogeneous. That which leads to rock typing of carbonate rocks is noteasy to do even by integrating static and dynamic properties of rocks. In accordance with the defi nition ofrock types that are commonly used, rocks or parts of rocks that have been deposited in the same environmentand experienced similar diagenetic process have similar physical characteristics, such as grain orrock fabric texture, pore geometry and structure pores, then the characters that will be used as the basisfor determining rock types. The use of rock fabric has been performed by many previous researchers. Whilethe use of attributes in the rock pores typing is still limited and more emphasis on engineering purposes.The objective of this study is to integrate all three of these characteristics in the determination ofrock typing. Theories that have been established and related to fl uid fl ow in capillaries and porousmedia that will be used to characterize the pore geometry and pore structure. Furthermore, thecharacteristics of the geological evidence will be conducted using core description, petrographyand other data to obtain the relationship between aspects engineering and aspects geology inaccordance with concept or defi nition of rock type in question. In rock typing, permeability and porosity characterize the pore geometry and pore structure. This study proves that there is a strongrelationship between the characteristics of the detail geological and architecture pores. Thus,the resulting methodologies rock typing can be universal with respect to aspects of geology andpetroleum engineering.